A review of medical termination of pregnancy profile in a tertiary care center - L., Veena; Sarojini, . (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The Medical Termination of Pregnancy Act (MTP Act) came into force from 01 April 1972 and again revised in 1975. The objective was to study demographic profile, methods, various indications and complications due to Medical Termination of Pregnancy performed in our institution. Methods: The present study was carried out in the Department of Obstetrics and Gynecology, BMCRI Bangalore India from November 2015 to October 2016 for 1year. After thorough history including reasons for MTP, detailed examination, investigations and consent, 522 women underwent MTP using various methods in one year at Vani Vilas hospital. Women were observed for any complications and then discharged. Results: In present study, 522 women fulfilling inclusion criteria underwent MTP. MTPs performed during 1st trimester was 411 (78.8%) and in mid-trimester were 111 (21.2%). Common indications for MTPs were contraceptive failure 262 (50.4%) followed by ‘to prevent grave injury to the physical and mental health of the pregnant women’ 112 (23.2%). 326 women underwent manual vacuum aspiration (MVA). Mid-trimester MTPs were done by Foleys with additional misoprostol 106 (20.4%). Overall complication rate was less 143 (27.3%). Most common complication found amongst the women who underwent MTP was Gastrointestinal 51 (9.7%). Conclusions: The most common reasons for medical termination of pregnancy (MTP) is unwanted pregnancy due to nonuse of contraceptives by the women of reproductive age group. There is a need to focus on unmet need for family planning services including medical termination of pregnancy (MTP) services.